Effect of multi wall carbon nanotube on electrical properties 4-[4-((S)-Citronellyloxy)benzoyloxy]benzoic acid liquid crystal host - Denktas, C.; Ocak, H.; Okutan, M.; Yildiz, A.; Eran, B. Bilgin; Koysal, O. (ELSEVIER SCI LTD, 2015)
Dielectric properties, conductivity mechanisms and current voltage characteristics of Multi Wall Carbon Nanotube (MWCNT) doped and pure Liquid Crystal (LC) material was investigated using impedance spectroscopy method in the frequency range of 100 Hz to 15 MHz. Liquid crystalline material, 4-[4-((S)-Citronellyloxy)benzoyloxy]benzoic acid (CBBA) as a host material and MWCNT was used as doping material in this study. In order to observe the effects of doping MWCNT into LC on dielectric properties, an MWCNT material was doped into CBBA structure with 1 wt%. Real part of dielectric constants (epsilon'), imaginary part of dielectric constant (epsilon ''), i.e. dielectric loss, dissipation factor/dielectric loss tangent (tan delta) were obtained for the pure and doped LC samples. In addition, dielectric strength (bads), negative dielectric anisotropy (Delta epsilon da), absorption coefficients (alpha) and relaxation times (tau) were calculated from the empirical data. I-V characteristics of pure LC and doped LC structures were carried out at micro-current levels by current-voltage measurements. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Carbon-carbon composites (CCCs); Physical properties; Electrical properties; Assembly; DIELECTRIC ANISOTROPY; CONDUCTIVITY; COMPOSITE; DISPERSION; DISPLAYS; Engineering; Materials Science